The value of grain sorghum harvested as silage and as dehydrated pellets - Richardson, D.; Smith, E.F.; Koch, B.A.; Tsien, W.S.; Boren, Fred W. (Kansas Agricultural Experiment Station, 2011)
Combine-type sorghum grain is widely grown in Kansas, and normally only the grain is harvested. In many instances, moisture conditions at harvest time are such that the grain cannot be stored without artificial drying. Sometimes there is danger of losing immature grain because of early frost. This test was planned to study the value of the entire grain sorghum plant harvested as silage and as dehydrated pellets.
Keywords: Beef; Grain sorghum; Silage; Dehydrated pellets